Social and Environmental Disclosures in the European Insurance Industry in Conditions of Flexibility in the Mandatory Reporting Regime - Ksenija Denčić-Mihajlov; Dejan Spasić (Amfiteatru Economic)
Insurance companies are expected to play a critical part in the transition to a net-zero, resilient, and socially just economy. Not only can they impact changes through sustainable investing and underwriting, but they can also make a contribution with their own sustainable and inclusive operations that go beyond traditional corporate social responsibility approaches. Both market and regulatory drivers in different European jurisdictions lead to various stages of the sustainability maturity of the insurance companies. Mandatory nonfinancial reporting in the European Union (EU) is codified by Directive 2014/95/EU, which allows a high level of flexibility, particularly in the choice of reporting standards/guidelines and disclosure methods. Although the Community Law has been further developed in the meantime, only with the adoption of Directive (EU) 2022/2464 a uniform reporting methodology based on the European sustainability reporting standards (ESRS) was established. The paper explores how European insurers have made progress in the sustainability agenda ahead of the adoption of Directive 2022/2464, in the flexibility regime of mandatory non-financial reporting. In a sample of 20 internationally active European insurance groups, we find that leading European insurers responded to the demands of stakeholders and society as a whole and provided high-quality information on social and environmental issues during the period 2016-2021. There is a significantly stronger focus on environmental issues, with the level of disclosure depending on the sustainability maturity stage and size of the insurance company